Consumptive Behavior in Online Shopping among Accounting Education Students at Universitas Muhammadiyah Surakarta - Sulistyaningrum, Anggun; Asmawan, Moh Chairil (Universitas Muhammadiyah Surakarta, 2024)
The aim of this research is to describe consumptive behavior in online shopping among accounting education students, find out the factors that influence consumptive behavior in online shopping among accounting education students and describe how to overcome consumptive behavior in online shopping among accounting education students. This research uses a qualitative approach. Data collection through observation, interviews and documentation. The subjects in this research were five accounting education students at universitas muhammadiyah surakarta. The techniques used in this research were data collection, data reduction, data presentation and conclusions. The results of this research show that 1) consumer behavior in students can be seen from their appearance or lifestyle such as usage style which is trending in the surrounding environment. 2) There are factors influencing the consumer behavior of accounting education students, namely social media. This is characterized by factors that influence consumer behavior in online shopping, advertising, discounts on social media can influence students to buy the product, apart from that, good packaging can attract students to own the product. 3) The impact of consumer behavior on students is that the higher the desire to own an item, the higher the expenditure, resulting in waste among students. To overcome this waste by resisting the desire to buy something that does not suit your needs, making a long-term financial budget, and saving.